Incidental endobronchial hamartoma in a patient with enchondroma - Kadamkulam Syriac, Arun (BMJ Case Rep, 2019)
Hamartomas are the most common type of benign tumours of the lung, constituting a small portion of all lung neoplasms. Hamartomas are rare benign tumours composed of multiple mesenchymal cell lines. Two clinical types have been defined according to the location: intraparenchymal and endobronchial, more frequently the former. We present a case of endobronchial hamartoma causing significant blockage of the right middle lobe. The finding was incidental on a CT scan of the chest done for staging purposes for a large mixed lytic and sclerotic lesion that was found within the proximal-mid portion of the tibial diaphysis. The endobronchial lesion was removed by hot electrocautery snare during bronchoscopy and identified as a hamartoma. Argon plasma coagulation was applied to the lesion’s base afterwards and the patient was to follow-up in 3 months for a repeat CT scan.